Light-matter interactions in high quality manganese-doped two-dimensional molybdenum diselenide - Liu, Sheng (2022)
Introducing magnetic dopants into two-dimensional transition metal dichalcogenides has recently attracted considerable attention due to its promising applications in spintronics and valleytronics. Herein we realized manganese-doped molybdenum diselenide (MoSe2) single crystal via chemical vapor transport (CVT) reaction, containing up to 2.9% (atomic concentration) Mn dopants, and investigated the light-matter interaction in these samples. We observed a suppressed trion intensity, a longer photoluminescence lifetime, and prominent blue- and red-shift of E2g2 (in-plane) and A1g (out-of-plane) Raman modes, respectively. Moreover, the Mn dopants increase the valley Zeeman splitting of the MoSe2 monolayer by ∼50%, while preserving the linear dependence on magnetic field. First-principles calculations indicate that the spin-polarized deep level defect states are formed due to the Mn substitutional dopants in the MoSe2 lattice. The resulting defect potential favors the funnelling of excitons towards the defects. The Mn dopants reduce the magnitude of the interatomic force constants, explaining the red-shift of the A1g mode. The Mn atoms and their immediate Mo and Se neighbors carry significant magnetic moments, which enhance the observed exciton g-factors due to the exchange interactions affecting defect-bound excitons.